2005
DOI: 10.1016/j.otohns.2005.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Sphenoid Sinus Disease: Etiology and Management

Abstract: The presenting symptoms of isolated sphenoid sinus disease can be nonspecific and may result in an inordinate delay in diagnosis. Nasal endoscopy and radiologic imaging are central to making an accurate and timely diagnosis. Medical treatment or minimally invasive surgical techniques can successfully manage the majority of patients with persistent or refractory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 18 publications
4
88
0
6
Order By: Relevance
“…A wide variety of other organisms can cause sphenoid sinusitis. In the study by Friedman, (4) twenty-five of the 29 patients with inflammatory sphenoid sinus lesions had positive cultures, 68% of the cultures were positive for bacteria with methicillin-resistant Staphylococcus aureus being the most common pathogen, followed by Pseudomonas aeruginosa. 32% of the cultures grew fungal organisms, with Aspergillus species being the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of other organisms can cause sphenoid sinusitis. In the study by Friedman, (4) twenty-five of the 29 patients with inflammatory sphenoid sinus lesions had positive cultures, 68% of the cultures were positive for bacteria with methicillin-resistant Staphylococcus aureus being the most common pathogen, followed by Pseudomonas aeruginosa. 32% of the cultures grew fungal organisms, with Aspergillus species being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…(2,4) Friedman et al (4) reviewed 50 patients with isolated sphenoid sinus lesions and 72% of the cases were due to inflammatory causes which included: chronic sinusitis 34%, fungal ball 20%, mucocele12%, acute sinusitis 4%, and chronic invasive fungal sinusitis 2%. Neoplasms were seen in 16% of patients (benign 10%, malignant 6%).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed theories for its development include cystic dilatation of glandular structures and cystic dilata- tion of embryonic epithelial remains. 7 Previous craniocerebral traumas and infl ammations (polypoid sinusitis) are considered to be the most likely reasons for the occurrence of mucocele. 8 Similar to the case of T. Adouly et al, a single risk factor for the occurrence of the disease was not found in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…8 Embryologically, AMV is the result of incomplete seperation of the mitral valve tissue from the endocardial cushion. 1,9,10 Two types of accessory valve tissue were defined by Faggian et al in 1983. 7 The mobile type is a parachute-like leaflet floating in the ventricular outflow tract.…”
mentioning
confidence: 99%
“…Nas situações inflamatórias, a esfenoidotomia por via endoscópica transnasal usando o corneto superior como referência é uma técnica considerada eficaz e segura. [9][10][11] Em casos específicos poderá realizar-se uma recessão parcial do corneto médio para melhor visualização. A abordagem transetmoidal poderá ser considerada em fossas nasais pouco amplas ou nos casos de patologia concomitante de outros seios perinasais.…”
unclassified